DESAIN BALIHO KAMPANYE MAHYELDI - AUDY DI PILGUB SUMBAR 2020 SEKARANG - Juwita Wirta Sri Depi; Hanafi Malik (Asosiasi Dosen Muda Indonesia, 2024)
This study analyzes the design of Mahyeldi - Audy's campaign billboard in the 2020 West Sumatra Gubernatorial Election using a qualitative approach with a literature study method. The analysis focuses on visual elements, typography, symbolism, and visual narratives used in the billboard design. The results show that the billboard design successfully combines traditional Minangkabau elements with a vision of modernity, creating a strong visual narrative about leadership rooted in local values yet oriented towards progress. The use of color, typography, and local symbolism demonstrates a deep understanding of the socio-cultural context of West Sumatra. The design's effectiveness lies in its ability to convey complex campaign messages through an easily digestible visual medium while building an emotional connection with voters. However, this design also raises critical questions about gender representation, identity politicization, and the ethics of visual political communication. This study contributes to the understanding of the role of visual communication in shaping political discourse and influencing voter behavior in an increasingly mature era of local democracy.